50th Anniversary of Adult Neurogenesis: Olfaction, Hippocampus and Beyond - Alino Martinez-Marcos (Frontiers Research Topics, 2016)
In the mid-sixties, the discovery by Altman and co-workers of neurogenesis in the adult brain changed the previous conception of the immutability of this organ during adulthood sustained among others by Cajal. This discovery was ignored up to eighty’s when Nottebohm demonstrated neurogenesis in birds. Subsequently, two main neurogenic zones were characterized: the subventricular zone of the lateral ventricle and the subgranular layer of the dentate gyrus. Half century later, the exact role of new neurons in the adult brain is not completely understand. This book is composed by a number of articles by leaders in the filed covering from an historic perspective to potential therapeutic opportunities.